Development of Wood Apple Pulp Scooping Mechanism - Dr. S. P. Divekar; S. A. Shegekar; Dr. V. P. Khambalkar; Chaitali D. Nikole (International Journal of Engineering and Management Research, 2020)
The physical properties of wood apple were measured to develop wood apple scooping mechanism. The developed of wood apple scooping mechanism consists of following components (i) scooping tool, (ii) fruit holder, sliding mechanism, (iv) pulp discharge chute and (v) driving mechanism. The scooping mechanism was evaluated for scooping of wood apple fruits with two scooping tools viz., 4 blades tool and 6 blade tool and at 3 rotational speeds viz., 350 rpm, 400 rpm, 450 rpm. The mechanism was observed to perform best with 4 blades scooping tool at the operating speed of 400 rpm. The best performance for pulp recovery percentage and rate of scooping were found to be 83.84 % and 37.80 Kg/h, respectively.